BARRIERS AND DRIVERS OF SOCIAL ENTERPRISE PERFORMANCE IN INDONESIA'S SOCIAL ENTERPRISES: A QUALITATIVE STUDY WITH OWNERS AND MANAGERS - Yusuf Iskandar; Joelianty; Umi Kaltum; Hilmiana (Universitas Nusa Putra, 2021)
Social enterprises are established to accomplish a specific social purpose. They not only focus on maximizing profits but also the benefits to society and the environment. The profits made are in most instances used to fund the social programs they run. Recently, social enterprises have attracted much attention from the public as well as researchers. This is the focus of this study. The specific target of this study is social enterprises in Indonesia. Social enterprises are gaining traction in many counties, and Indonesia has not been left behind. Millennials in Indonesia are leading in creating businesses that are meant to create positive social and environmental impacts. Social enterprises in Indonesia need legitimacy. They need to be able to communicate their hybrid identities to stakeholders without fear of being rejected. To access the funds and skills they need, social enterprises need to show how they are performing so that the stakeholders understand. This study discusses three important issues regarding the performance of social enterprises in Indonesia. One is intellectual capital which is defined as knowledge that can be converted into value. It refers to the flow of knowledge within an organization, which is the sum of everything that people know that makes it operate efficiently. Another is the social entrepreneurial orientation (SEO), which refers to the combination of social missions with entrepreneurial actions to achieve social firms' sustainability. The third is dynamic capabilities, which refers to enabling companies to transform and change according to times. Through the development of these capabilities, the organization can achieve a solid last competitive advantage. Lastly, there is a competitive advantage which is the ability of a firm to perform better than others in the market. Interviews with 50 managers and owners of social enterprises in Indonesia have effectively covered factors affecting performance.